Five-finger hypnosis and foot-soaking therapy to reduce anxiety in pre-eclampsia mother - Kurniawati, Dini; Septiyono, Eka Afdi; Mangrasih, Rhozy Sadya; Tama, Fahma Ilmi Nawa (Jurnal Kesehatan Ibu dan Anak, 2019)
Depression and anxiety in early pregnancy are associated with the risk of pre-eclampsia. Anxiety management can be a variety of ways, including pharmacological and non-pharmacological therapy like non-pharmacological therapies such as five- finger hypnosis and foot-soaking therapy. This study aims to determine differences in anxiety levels in five-finger hypnosis and foot-soaking therapy in pregnant women with pre-eclampsia. The study design used pre-experimental. Sampling techniques used cluster sampling with 120 respondents with the characteristics of pregnant women with pre-eclampsia who underwent treatment at the health center in the Besuki Raya. The instrument for measuring maternal anxiety used the Hamilto Rating Scale for Anxiety. Data analysis used an independent t-test with a significance level of 0.05. The results of the Independent T-test stated that there was a difference between the average anxiety of the respondents who carried out five-finger hypnosis interventions and foot-soaking interventions {t= (-8.485); p= 0.0001; 95% CI= (-5.838) - (-3.629)}. The average anxiety of mothers with pre-eclampsia after a five-finger hypnosis intervention (Mean different= 5.60) or foot soak (Mean different=1.17) states the lowest average anxiety was after a five-finger hypnosis intervention. Intervention hypnosis five fingers and a foot soak is a complementary therapy that has many benefits, and there are no harmful side effects